Entrepreneurship-Based Biotechnology E-Module Development to Improve Critical and Creative Thinking Skills (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2022)
Courageous learning triggers learning loss, which is characterized by a decrease in the ability to think critically and creatively. The solution used with innovation in learning media is the e-model of entrepreneurship. This study aims to test the feasibility of entrepreneurship-based biotechnology e-modules and improve students' critical and creative thinking skills after using this e-module. This research and development (RD), which applies the 4D model (Define, Design, Develop, and Dissemination). The study consisted of 31 class IXA students of yunior high school. The research instrument consisted of expert validation questionnaires, pretest-posttest questions, and student response questionnaires. The analysis of the validation questionnaire for material and media experts produced an average score quite high with the appropriate criteria for use in classroom learning. The results of the t-test for students' critical and creative thinking skills yield a significant value of 0.0 which is smaller than 0.05, which means that there is a significant difference between students' critical and creative thinking skills in the pretest and post-test. Analysis of the N-gain value of students' critical and creative thinking abilities shows an average result of 0.46. This result is included in the category of moderate improvement, which means that the increase in students' critical and creative thinking skills is in the medium category. This e-module also has a very good response from all students. Based on the results of these analyses, the entrepreneurship-based biotechnology e-module is declared feasible for use in learning and can improve students' critical and creative thinking abilities.